The Effectiveness of Digitalization in Family Caregiver Empowerment Model (FCEM) for Reducing Diabetes Incidence in Rural Areas: An App-Based Literature Review Study - Wildana, Fahmi; Lutfian, Lutfian; Azizah, Aufa; Wardika, Izdihar Javier; Ramadhani, Fariza Barika; Utomo, Wahyu Dwi (Jurnal Ilmiah Kesehatan, 2024)
Diabetes mellitus (DM) is a condition characterised by anomalies in insulin production, action, or both, which result in hyperglycemia and insufficient management of blood glucose levels. Patients, their families, and the healthcare system must bear a heavy burden when it comes to the long-term management of diabetes mellitus (DM) via medication and lifestyle changes. To lower the prevalence of diabetes, especially in rural regions, this project aims to explore the possibility of incorporating the Family- Centered Empowerment Model (FCEM) into a digital application. Using a literature review technique, this study gathered information from books, articles from relevant organizations, and journal publications. The search was conducted using keywords like Empowerment, Family, Diabetes, Telehealth, and FCEM to find sites that fit the inclusion requirements. According to the findings, the FCEM intervention significantly improves quality of life, psychological management, physical activity, and health education in addition to encouraging lifestyle changes. Additionally, it raises health literacy, which boosts psychological support, increases adherence to blood sugar management, and lessens disease-related anxiety.